Regenerative medicine, resource and regulation: lessons learned from the remedi project. (March 2011) - Ginty, Patrick J; Rayment, Erin A; Hourd, Paul; Williams, David J
The successful commercialization of regenerative medicine products provides a unique challenge to the manufacturer owing to a lack of suitable investment/business models and a constantly evolving regulatory framework. The resultant slow translation of scientific discovery into safe and clinically efficacious therapies is preventing many potential products from reaching the market. This is despite of the need for new therapies that may reduce the burden on the world''s healthcare systems and address the desperate need for replacement tissues and organs. The collaborative Engineering and Physical Sciences Research Council (EPSRC)-funded remedi project was devised to take a holistic but manufacturing-led approach to the challenge of translational regenerative medicine in the UK. Through strategic collaborations and discussions with industry and other academic partners, many of the positive and negative issues surrounding business and regulatory success have been documented to provide a remedi-led perspective on the management of risk in business and the elucidation of the regulatory pathways, and how the two are inherently linked. This article represents the findings from these discussions with key stakeholders and the research into best business and regulatory practices.